Anisakiasis Causing Acute Dysentery in Malaysia - Amir, Amirah (Am J Trop Med Hyg, 2016)
Human anisakiasis is a zoonosis acquired by eating raw or undercooked infected seafood. Herein, we report a case of acute dysentery caused by anisakiasis in a 64-year-old man in Malaysia. A colonoscopy was performed and a nematode larva was found penetrating the mucosa of the ascending colon. Bleeding was observed at the site of penetration. Y-shaped lateral epidermal cords were seen from the cross section of the worm, which is a prominent feature of Anisakis larva. Molecular analysis using polymerase chain reaction of cytochrome oxidase 2 (cox2) gene confirmed the specimen to be larva of Anisakis simplex.